RECHERCHES ET EXPERIENCES POURSUIVIES DANS LE BUT DE TROUVER DE NOUVEUES FIBRES SYNTHETIQUES POUVANT SERVIR A LA CONFECTION DE MADRAGUES MARITIMES - Jelescu, Nicolae; Elefteriu, R. (Cercetări Marine - Recherches Marines, 2026)
In the first part of the paper the authors refer to the object of Investigations and the work so far for its fulfilment, taking Into account the complexity of aspects that should be observed when evaluating yarns and fibres used in the manufacture of trap nets. In the second part, the variance in the breaking load for every type of synthetic yams tested so far is graphically. The results are suggestive for the conclusions of the work.